Geology Adjacent to the Alaska Highway between Fort St. John and Fort Nelson, British Columbia: - Hage, Conrad Olai, 1901- (Author); Geological Survey of Canada (Author) (Geological Survey of Canada, 1944)
by C.O. Hage. Paper (Geological Survey of Canada) 44-30.